Magnetocaloric energy conversion : from theory to applications /: from theory to applications. ([2015]) - Kitanovski, Andrej; Tušek, Jaka; Tomc, Urban; Plaznik, Uroš; Ožbolt, Marko; Poredoš, Alojz
No abstract available